Dynamics of charge‐pump phase‐locked loops. (19th April 2012) - Curran, Paul F.; Bi, Chuang; Feely, Orla
ABSTRACT Certain problems in the existing treatment of the stability of charge‐pump phase‐locked loops are identified and addressed in this work. New results concerning the instability, stability, and asymptotic stability of charge‐pump phase‐locked loops are obtained by means of Lyapunov's direct and indirect methods. Closer consideration of the local dynamics provides further insight into the system's patterns of behavior. In particular, the influence of circuit parameters on the nature of the steady‐state orbits is investigated. Copyright © 2012 John Wiley & Sons, Ltd.